Traction Alopecia: Clinical and Cultural Patterns - Khalifa E Sharquie; Robert A Schwartz; Wesal K Aljanabi; Camila K Janniger (Wolters Kluwer Medknow Publications, 2021)
Background: Traction alopecia is common and preventable but frequently overlooked disorder. Objective: To evaluate patients with traction alopecia. Patients and Methods: This study was conducted at the Dermatology Center, Medical City, Baghdad, Iraq, during the period from November 2005 to October 2019. Demographic features like age, gender, disease duration and special hair styling practices and accessories were recorded. Clinical patterns were studied. Results: Thirty female patients were included in this study. Their ages ranged from 6 to 47 years with mean age ± SD was 15.63 ± 9.806. Twenty-one (70%) were below the age of 16 years. No patient had tightly curled hair. All cases were asymptomatic apart from hair loss. The fringe sign was observed in 27 (90%) of cases. The response to therapy was poor. Conclusion: Traction alopecia is an important type of pressure-induced hair loss evident in children and adults with or without curly hair due mainly due to cultural hair styling practices with its frequency apparently increasing in recent years. The fringe sign is common and of diagnostic importance. It is a preventable form of hair loss which can be reversed if diagnosed early; otherwise, permanent scarring alopecia results. It represents a pressure phenomenon evident worldwide in both non-Sub-Saharan lineage and Sub-Saharan lineage individuals.